Spatially resolved stellar populations with SAMI. Issue Volume 10:Issue S309(2014) (9th February 2015) - Scott, Nicholas
Abstract: Using data from the SAMI Galaxy Survey we measure azimuthally averaged stellar age and metallicity profiles for ∼ 500 galaxies, using both luminosity-weighted Lick indices and mass-weighted full spectral fitting. We find a weak trend for steeper (i.e. more negative) metallicity gradients in more massive galaxies, however, below stellar masses ∼ 10 10.5 M⊙, the scatter in metallicity gradient increases dramatically.